2009
DOI: 10.1002/jctb.2294
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of alcohol using emulsion liquid membrane consisting of paraffin oil as an organic phase and lecithin as a surfactant

Abstract: BACKGROUND: This paper reports on the use of a liquid emulsion membrane involving paraffin light oil as membrane phase and lecithin as surfactant for the extraction of alcohol from anthocyanin extract and simulated pineapple wine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
(27 reference statements)
2
16
0
Order By: Relevance
“…This contributed to a greater number of droplets and bigger mass transfer area that resulted in the highest extraction (95%) and the lowest swelling (5%). These findings are similar to another research that revealed very small swelling at the concentration of 3% w/v [29].…”
Section: Resultssupporting
confidence: 92%
“…This contributed to a greater number of droplets and bigger mass transfer area that resulted in the highest extraction (95%) and the lowest swelling (5%). These findings are similar to another research that revealed very small swelling at the concentration of 3% w/v [29].…”
Section: Resultssupporting
confidence: 92%
“…If the speed is constant then it will reduce the extraction due to improper mixing of phases. The treatment ratio 1:1 resulted in maximum extraction of imidazole from dilute aqueous solutions, alcohol from aqueous solution and lipase from crude extract …”
Section: Resultsmentioning
confidence: 99%
“…Further increase in stirring speed resulted in decrease in activity recovery and purification fold. It may explained on the fact that the increase in the stirring speed up to a certain extent (450 rpm) results in the formation of smaller sized emulsion droplets leading to enhanced surface area for mass transfer . Further increase in stirring speed adversely affects stability of emulsion globules resulting in breakage, which might have resulted in the decrease in activity recovery and purification fold.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The work on the liquid membrane was initiated by Li [25] and further investigated by many researchers for the recovery of metal ions [15] as well as organic compounds [26]. Emulsion liquid membrane system, supported liquid membrane system, bulk liquid membrane system are the most commonly used types of liquid membrane systems commonly used for the extraction [27,28].…”
Section: Introductionmentioning
confidence: 99%